Explaining turnover of auditors from the Big Four Accounting Firms in Singapore. - Lee, Wendy Hui Yi. (2008)
This study sets out to reserach the turnover intention of auditors of the Big Four Accounting firms in Singapore, as there are currently few research studies on auditors.